Enhancing Manufacturing Processes through Data Analytics in Mastercam Setup Sheets - V. V. Shukla; P. V. Sawalakhe; J. A. Shaaikh; M. G. Trivedi; N. P. Gudadhe (Research and Developments in Engineering Research Vol. 2, 2023)
This chapter focuses on the benefits of utilizing simulation and modeling for data analytics in smart manufacturing. The authors highlight the usefulness of simulation models in facilitating data analytics for various sectors, including logistics, management, transportation, health systems, and manufacturing. The chapter emphasizes the importance of having an evaluation and management system that can adapt to changing operations planning, production configurations, and manufacturing system development. The authors suggest that traditional static production planning methods are not sufficient for this purpose and that dynamic and accurate prototypes of production are necessary, which can be achieved through simulation models that incorporate real shop floor and production network data. This article highlights the advantages of using simulation and modeling for data analytics in smart manufacturing. Simulation models can aid in data analytics for various industries, including logistics, management, transportation, health systems, and manufacturing. It emphasizes the importance of having an evaluation and management system that can adapt to changing operations planning, production configurations, and manufacturing system development. Traditional static production planning methods are insufficient for this purpose, and dynamic and accurate prototypes of production are necessary. Simulation models can incorporate real shop floor and production network data, providing accurate and real-time estimations of process efficiency. For organizations that use Setup sheets generated by Mastercam, managing the large amounts of data for all the machining processes can be a challenge. However, customizing the machining data can help programmers understand and perform job setting and operations, while supervisors can improve product flow efficiency by using minimal documentation. Customized setup sheets can also reduce the time required for each operation and provide accurate real-time and estimated time comparisons for proper analysis of process efficiency. In general, job setup and tool orientation are defined in a user-friendly manner, ensuring accuracy and ease of use. By reducing the size of sheets while maintaining essential data, organizations can effectively manage revisions of the database with optimum efforts. The customization of machining data can improve process efficiency and accuracy while reducing the time required for each operation. The article concludes that utilizing simulation and modeling for data analytics in smart manufacturing can provide numerous benefits, including improved process efficiency, accuracy, and real-time estimations. Customizing machining data and setup sheets can reduce the time required for each operation and aid in analyzing proper working of processes. These technologies can provide a competitive edge for organizations and contribute to their success.